Metallothioneins in Earthworms: The Journey So Far - Ogunlaja Aemere; Vikas Sharma; Johnson Lin (Open Journal of Environmental Biology - Peertechz Publications, 2020)
Earthworms play important roles in terrestrial ecosystems including evaluating the health status of the soil in environmental studies. Its regulation and detoxification of metallic metals and the non-essential metal ion are associated with the possession of Metallothioneins (MTs). Three isoforms of MTs are induced in some species of earthworms under stress in the soil; wMT1, wMT2, and wMT3 (found in cocoons). Though reports on the nucleotide sequences, mechanisms of action and entire functions of two earthworm MTs isoforms exist, the precise mechanism of action and entire functions of wMT3 are still obscure. Metals and stress are known inducers of MTs in earthworms. In recent times, Contaminants of Emerging Concerns (CECs) and the advent of nanotechnology has occasioned a handful of studies evaluating their effect in the environment using biomarkers like metallothioneins. More research focusing on CECs' and nanoparticles' ecotoxicological impact in the environment by monitoring biomarkers like earthworm metallothioneins is encouraged. The detection and quantification of MTs involve a wide array of techniques including analytical, instrumentation and molecular analyses which remains the most commonly used. This review evaluates the various methods and highlights their pros and cons.